2019
DOI: 10.1002/cncr.31782
|View full text |Cite
|
Sign up to set email alerts
|

Survival after a cancer diagnosis among solid organ transplant recipients in the United States

Abstract: BACKGROUND: Transplant recipients have an elevated risk of cancer because of immunosuppressive medications used to prevent organ rejection, but to the authors' knowledge no study to date has comprehensively examined associations between transplantation status and mortality after a cancer diagnosis. METHODS: The authors assessed cases in the US general population (N=7,147,476) for 16 different cancer types as ascertained from 11 cancer registries. The presence of a solid organ transplant prior to diagnosis (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 31 publications
6
64
0
6
Order By: Relevance
“…Prior studies have demonstrated increased rates of cancer‐related mortality in solid organ transplant recipients, as would be expected, including for head and neck cancers, but again most studies have been hampered by the lack of a control group, making survival comparisons difficult . However, two recent studies have utilized cancer databases to compare cancer patients with transplants to those without: each found a higher rate of cancer‐specific mortality for transplant recipient with certain head and neck cancers . The largest study found increased cancer‐specific mortality in oral cavity/pharynx, but not for thyroid; in the present study, we found significantly worse survival in thyroid patients, but we assessed OS, not cancer‐specific mortality, making comparison of findings challenging .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Prior studies have demonstrated increased rates of cancer‐related mortality in solid organ transplant recipients, as would be expected, including for head and neck cancers, but again most studies have been hampered by the lack of a control group, making survival comparisons difficult . However, two recent studies have utilized cancer databases to compare cancer patients with transplants to those without: each found a higher rate of cancer‐specific mortality for transplant recipient with certain head and neck cancers . The largest study found increased cancer‐specific mortality in oral cavity/pharynx, but not for thyroid; in the present study, we found significantly worse survival in thyroid patients, but we assessed OS, not cancer‐specific mortality, making comparison of findings challenging .…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, as previous studies have primarily assessed only transplant patients without comparators, the effects of solid organ transplant on head and neck cancer survival is uncertain. A few studies have demonstrated that transplant patients with cancer have worse survival compared with other cancer patients, but research is limited …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by D'Arcy et al ., with similar design to ours, 7,147,476 cancer cases (of which 11,416 among OTRs) diagnosed 1987–2014 were identified from 11 US cancer registries and followed for cancer‐specific mortality. Comparing rates of cancer‐specific death among OTRs and non‐OTRs, the authors found significantly elevated HRs for melanoma, high‐grade lymphoma, breast, colorectal and bladder cancer, in line with our results.…”
Section: Discussionmentioning
confidence: 79%
“…Poorer survival has been attributed to inhibition of the immune response to melanoma due to immunosuppression and may suggest treatment algorithms developed for the general population may not be effective in transplant recipients. Transplant recipients in the US with melanomas are also less likely to undertake surgery, radiotherapy or chemotherapy compared to the general population . Whether this is the case for Australian and New Zealand given differences in healthcare systems, needs further investigation.…”
Section: Discussionmentioning
confidence: 99%